Structural biomacromolecules in plants : what can be learnt from the fossil record? - Sinninghe Damsté, J.S.; Bergen, P.F. van; Blokker, P.; Collinson, M.E.; Leeuw. J.W. de (Elsevier, 2003)
The invasion of the land by plants may have forced the evolution of specific physiological adaptation to survive this hostile new environment. Two of the main problems plants had to overcome included an increase in the levels of UV radiation and water loss or desiccation. Studying the resistant macromolecular composition of outer coverings and strengthening tissues from both modern and fossil examples can reveal information on the molecular evolution of these structures. The resistant molecules in cuticles (i. e. cutin and cutan) and spore and pollen walls (sporopollenin) are all based on even carbon numbered long-chain aliphatic chemical building blocks providing sufficient hydrophobicity to reduce water loss These aliphatic moieties are largely similar to those present in the resistant walls of algae (algaenan) from which the land plants may have evolved. Apart from the aliphatic material, sporopollenin and, to some degree, cutin and cutan from both modern and fossil examples also reveal the presence of cinnamic acids, which probably are responses to the enhanced levels of UV radiation on land. With respect to the strengthening tissues, lignin may have been an important biomolecule in early land plants but, to date, no unequivocal molecular evidence exists that it actually occurred in the oldest land plants. Moreover, molecular data from modern strengthening tissues indicate that lignin is not necessarily a physiologic prerequisite for the evolution of plant tissues that provide physical strength and that other phenolic macromolecular biomolecules may have played an additional (key) role in the evolution of the early land plants.
Keywords: Aardwetenschappen